Pengaruh Media Loose Parts terhadap Perkembangan Motorik Anak Usia 4-5 Tahun - Azizah, Rifa Fauziyatul; Nugraha, Anggi Purwa (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2025)
This study aims to examine the effect of loose parts media on fine motor development in children aged 4–5 years at TK Sabilul Huda. The research employed an experimental method with a One Group Pretest-Posttest design involving 12 children. Data were collected through structured observations using fine motor skill assessment instruments and analyzed using descriptive and inferential quantitative methods. Results indicated significant improvement following loose parts implementation. In the pretest, 75% of children were categorized as Not Yet Developed and 25% as Starting to Develop. Post-treatment, 41.7% of children achieved the Developing as Expected category and 58.3% reached Very Well Developed. N-gain analysis showed an average of 0.797 (high category), while the Wilcoxon test yielded p = 0.002157 < 0.05. Therefore, it can be concluded that loose parts media effectively improves fine motor skills in early childhood.